Comparison of Intraoperative Hemorrhage by Blunt Versus Sharp Expansion of Uterine Incision at Lower Segment Cesaeren Delivery - Humaira Shaheen, Sadia Zahoor, Nadia Zulfiqar, Bilqees Akhtar Malik, Zafar Iqbal, Muhammad Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the intraoperative hemorrhage between blunt and sharp expansion of uterine incision at lower segment caesarean delivery. Study Design: Randomized controlled trial. Study Duration: 03-02-2022 to 02-08-2022 (6 months) Setting: Department of Obstetrics and Gynecology, D.G Khan Hospital D. G Khan Material and methods: Total 74 patients undergoing C-section, age range 20-40 years, with singleton pregnancy and patients with >37 weeks gestation. (on ultrasound) were included. Intraoperative blood loss was compared between blunt and sharp group. Results: Mean age was 32.31 ± 6.246 years, in Blunt and Sharp group, mean age was 35.70 ± 4.122 years and 28.92 ± 6.202 years. In Blunt group, mean blood loss was 201.62 ± 60.794 ml while in sharp group was 782.03 ± 153.819 ml. Difference of mean blood loss between Blunt and Sharp group was significant (P= 0.000). Conclusion: Results of present study reflects that there is significant difference of intraoperative mean blood loss between blunt and sharp groups. Most of the patients were between 31-40 years of age. After stratification of age, gestational age, parity and type of C-section, it was found that there is significantly low mean blood loss in blunt group as compared to sharp group. Keywords: Blood loss, C-section, Blunt, intraoperative haemorrhage,